2023
DOI: 10.3390/su152215783
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Flexural Response of Palm Shell Aggregate Lightweight Reinforced Concrete Beam

Md. Habibur Rahman Sobuz,
Md. Saiful Islam,
Abu Sayed Mohammad Akid
et al.

Abstract: This work focuses on examining the mechanical characteristics and flexural response of reinforced concrete (RC) beams by incorporating oil palm shell (OPS) lightweight aggregate from oil palm shell waste. The OPS aggregates are replaced in various percentages, such as 0 to 50% of natural coarse aggregate (NCA). Mechanical properties of OPS concrete were conducted, and these properties were used to quantify the flexural performance of RC beams. Five RC beams with several gradations of OPS aggregates were cast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous investigations have shown that the incorporation of steel fibers into LWC substantially enhances its compressive strength. Similarly, it has been reported that the addition of steel fibers to Oil palm shell concrete (OPSC) also increases its compressive strength [43,44]. Previous studies have shown the use of expanded clay aggregate to increase the compressive strength of LWC [45].…”
Section: Compressive Strengthmentioning
confidence: 90%
“…Previous investigations have shown that the incorporation of steel fibers into LWC substantially enhances its compressive strength. Similarly, it has been reported that the addition of steel fibers to Oil palm shell concrete (OPSC) also increases its compressive strength [43,44]. Previous studies have shown the use of expanded clay aggregate to increase the compressive strength of LWC [45].…”
Section: Compressive Strengthmentioning
confidence: 90%